Stigmatisasi Ata polo, Orang dengan Kekuatan Magis: Tantangan Berkatekese dalam Masyarakat Ngadha, Flores - Niba, Yulianus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2019)
The article explores the stigmatization phenomena of Ata polo, the ones with magical power in Flores, particularly in the District of Ngada. It is a great challenge for everyone who has to catechise the Catholics in the area. The Catholic Church is expected to take this socio-religious phenomenon into consideration and could offer an appropriate pastoral guideline for the people. In his research the writer found out that the ata polo labeling is merely an accusation based on suspicion on the one hand. On the other hand, he presumes that behind the magical practice, which is just a superstition, the people are looking for some personal interests or advantages.